A Bayesian Approach to Asset Valuation and Audit Size - Scott, William R. (Journal of Accounting Research, 1973)
There now exists a relatively large body of literature dealing with statistical sampling in auditing. This literature is mainly classical, in the sense that the auditor subjectively specifies desired confidence intervals1 and confidence levels as the basis for designing his audit sample.2 In specifying a confidence level, the auditor should take his evaluation of the adequacy of the firm's internal control into account, i.e., better internal control allows a lower audit size and enables the auditor to accept the resulting lower level of confidence in his estimates. However, no formal mechanism exists for linking the auditor's prior assessment of internal control and his sample design. Rather, this is left to the auditor's judgment.3 The lack of such a mechanism is a major defect of the classical approach to statistical sampling in auditing.